2021
DOI: 10.1007/s00520-021-06012-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among advanced cancer patients in Vietnam: a multicenter cross-sectional study

Abstract: Purpose Cancer is a leading cause of death in Vietnam. To maximize quality of life (QOL) at the end of life, valid and clinically useful instruments are needed to assess palliative care needs and the effectiveness of palliative care interventions. Methods We aimed to (i) determine psychometric properties of the Vietnamese version of the WHO abbreviated quality of life scale (WHOQOL-BREFVN) among advanced cancer patients, (ii) measure HR-QOL, and (iii) iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…lowest, but still adequate, Cronbach's α was Social Relationships. This finding is consistent with the results of the initial standardization of the instrument in the Greek language (Ginieri-Coccossis et al, 2012), and with other studies, in which the Cronbach's α for this domain was even lower (de Mol et al, 2018;Lin et al, 2019;Huyen et al, 2021). One possible explanation is the small number of items in the Social Relationships domain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…lowest, but still adequate, Cronbach's α was Social Relationships. This finding is consistent with the results of the initial standardization of the instrument in the Greek language (Ginieri-Coccossis et al, 2012), and with other studies, in which the Cronbach's α for this domain was even lower (de Mol et al, 2018;Lin et al, 2019;Huyen et al, 2021). One possible explanation is the small number of items in the Social Relationships domain.…”
Section: Discussionsupporting
confidence: 91%
“…The psychometric properties of this instrument have been evaluated in patients with a variety of types of cancer and at different phases of the disease progression (Van Esch et al, 2011;Lin et al, 2017), but to the best of our knowledge, there is little documentation of its psychometric properties in patients with advanced cancer. A recent study testing the psychometric characteristics of the WHOQOL-BREF in patients with advanced cancer in Vietnam recorded excellent internal consistency, reliability, and discriminant validity (Huyen et al, 2021), and satisfactory psychometric properties of this instrument were also demonstrated in a sample of patients with advanced stage lung cancer (de Mol et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…In the present study, the ECOG score ranked first in the nomogram. Other studies also demonstrated the association between ECOG score and HRQoL among advanced cancer patients (37,38). In the present study, targeted therapy was found to be a positive contributor to improving HRQoL among lung cancer patients.…”
Section: B Asupporting
confidence: 76%
“…In our nomogram, we also included four model predictors, because a higher ECOG score, no targeted therapy, a higher anxiety score, and a larger number of comorbidities were associated with poorer HRQoL. Previous studies had already demonstrated that ECOG scores were closely relevant to HRQoL (35)(36)(37)(38). For example, Daly et al (35) showed that an ECOG score of 3 or 4 was independently related to poorer HRQoL among incurable cancer patients, and the odd ratio could be up to 14.33, indicating the importance of the variable.…”
Section: B Amentioning
confidence: 99%
“…By gauging cancer patients’ satisfaction with their care journey, health care providers can identify areas for improvement, leading to better patients’ experiences and potentially even improved health outcomes. Previous studies among Vietnamese cancer patients primarily focused on health-related quality of life in both newly admitted and established cancer patients [ 10 , 11 ], with specific diagnoses such as gastric cancer [ 12 ] and breast cancer [ 13 ]. The healthcare facilities in Vietnam are divided into four levels, corresponding to a hierarchical administrative organization: communal, district, provincial, and national/central.…”
Section: Introductionmentioning
confidence: 99%